Fundamentals of library supervision - Giesecke, Joan (American Library Association, 2005)
The book explains how to create a productive workplace as they weave expert advice and commentary into an easy-to-use resource. This revised edition focuses on daily, real-world practices offering: specific strategies for new supervisory staff; hundreds of tips for encouraging a positive work ethic, maintaining productivity, and building teamwork; proven advice on practical supervisory issues like hiring, firing, interviewing, and training; and, policies and procedures that maintain fairness while addressing potential legal landmines. Guiding supervisors through the intricate process of managing others, this comprehensive handbook addresses the fundamental issues facing new managers. It also serves as a welcome refresher and reference for experienced managers facing new challenges in this complex and changing environment